Implementation of Guided Imagery to Reduce Anxiety in Patients with Breast Cancer - Irwansjah, Nurhasana; Amir, Haeril; Suharto Putri, Suci Hardianti; Marini , Erna (An Idea Nursing Journal, 2025)
Anxiety is one of the most common psychological problems experienced by preoperative patients, particularly those with breast cancer (Ca Mammae). This condition can increase sympathetic responses, worsen physiological conditions, and reduce patient readiness for surgery. Guided imagery is a non-pharmacological intervention that can help reduce anxiety through directed visualization, promoting relaxation and emotional calmness. This study aims to describe nursing care for patients with preoperative anxiety using the SDKI, SIKI, and SLKI standards and to identify the effectiveness of guided imagery in reducing anxiety levels. This case study employed a descriptive approach involving one patient with Ca Mammae (Mrs. S) scheduled for Modified Radical Mastectomy (MRM). Anxiety levels were measured using the Zung Self-Rating Anxiety Scale (SAS). Initial assessment showed moderate anxiety with a score of 45, accompanied by symptoms of restlessness, tension, difficulty concentrating, and increased motor activity. Nursing interventions followed the SIKI Anxiety Reduction (I.09314), including education, observation, emotional support, and guided imagery implementation. After the intervention, the anxiety score decreased to 35 (mild anxiety), and the patient appeared calmer, more cooperative, and able to better divert attention. The findings indicate that guided imagery is effective in reducing preoperative anxiety in Ca Mammae patients and can serve as a simple, safe, and beneficial complementary nursing intervention in clinical practice..